Expert System for Competences Evaluation 360° Feedback Using Fuzzy Logic. (24th July 2014) - Aguilar Lasserre, Alberto Alfonso; Lafarja Solabac, Marina Violeta; Hernandez-Torres, Roberto; Posada-Gomez, Rubén; Juárez-Martínez, Ulises; Fernández Lambert, Gregorio
Abstract : Performance evaluation (PE) is a process that estimates the employee overall performance during a given period, and it is a common function carried out inside modern companies. PE is important because it is an instrument that encourages employees, organizational areas, and the whole company to have an appropriate behavior and continuous improvement. In addition, PE is useful in decision making about personnel allocation, productivity bonuses, incentives, promotions, disciplinary measures, and dismissals. There are many performance evaluation methods; however, none is universal and common to all companies. This paper proposes an expert performance evaluation system based on a fuzzy logic model, with competences 360° feedback oriented to human behavior. This model uses linguistic labels and adjustable numerical values to represent ambiguous concepts, such as imprecision and subjectivity. The model was validated in the administrative department of a real Mexican manufacturing company, where final results and conclusions show the fuzzy logic method advantages in comparison with traditional 360° performance evaluation methodologies.